The effect of exogen glutathione administration on the gastric mucosal barrier in rats under stress - Zeki KANAY,; Cemil SERT,; Birgül IŞIK,; Doğan KURT,; Cihat GÜZEL,; Nuriye METE, (Turkish Journal of Gastroenterology, 2019)
-